Upaya Meningkatkan Hasil Belajar Siswa Kelas III Pada Mata Pelajaran Ilmu Pengetahuam Alam (IPA) Di SDK Wilain Dengan Menggunakan Metode Kooperatif TGT (Team Games Tournament) - Efrems Hendro Loe Loko (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
Education is a means and container for developing human resources (HR), therefore it needs to get attention and support from both the government, community and family. In the world of education today there are still many learning methods that use conventional learning models, namely students only listen to the teacher explaining the subject matter, without any action or activity as a learning experience. Learning activities like this, cause the results achieved by students in learning are not maximized, because students are only able to memorize facts, concepts, principles and theories. This study discusses efforts to improve student learning outcomes through TGT type cooperative learning. This study aims to obtain information about improving science learning outcomes for third grade students in the 2022/2023 school year through cooperative learning of the TGT type. The formulation of the problem in this study is: can the learning outcomes of class III students at SDK WILAIN be improved through the TGT Cooperative model. The object of research in this study were all Class III students of SDK WILAIN, totaling 16 people. The research instruments used in data collection were observation guidelines and test results after the action was taken. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis. Based on the initial survey conducted by the author, teachers who only used the lecture method resulted in low interest in learning and student learning outcomes in class III. Likewise for science subjects at SDK WILAIN, according to the documentation in the form of subject scores obtained from subject teachers, only 5 people (31.25%) out of 16 students showed high interest in learning that met the KKM (Minimum Completeness Criteria determined by For this reason, a new learning strategy is needed to improve the quality of the science learning process so that it has an impact on student learning outcomes.By using the Team Games Tournament (TGT) cooperative learning method, it is hoped that it can increase student learning interest. The results showed that there was an increase in student learning outcomes before and after the implementation of the TGT cooperative model. The score of students' interest in learning in class III SDK WILAIN before applying the cooperative model was 31.25%, which met the minimum completeness criteria or were in the low category. While the learning outcomes of third grade students at SDK WILAIN after implementing the TGT cooperative model were 87.5% which were in the high category. So the application of the TGT cooperative model can improve the learning achievement of class III students at SDK WILAIN.